Where did the universe come from? and other cosmic questions : our universe, from the quantum to the cosmos - Ferrie, Chris; Lewis, Geraint F. (Sourcebooks, 2021)
"Have you ever wanted to travel to the edge of the universe? What about getting sucked up into a black hole? For fans of Astrophysics for People in a Hurry comes an accessible science narrative that invites readers to eavesdrop on a conversation between two scientists as they dive into a multidisciplinary discussion of our understanding of the universe. Explore the depths of our universe, both known and unknown, with two award-winning physicists, Chris Ferrie and Geraint F. Lewis, as they examine the universe through the uniquely accessible lenses of quantum physics and cosmology, tackling questions such as: Where did the universe come from? Do black holes last forever? What is left for humans to discover? A brief but fascinating exploration of the vastness of the universe, Where Did the Universe Come From? And Other Cosmic Questions will have armchair physicists, astral enthusiasts, and reluctant science readers turning the pages until their biggest and smallest questions about the cosmos have been answered." --